Identity in Sherman Alexie's Indian Killer - Štěpánková, Šárka (Univerzita Pardubice, 2018)
The bachelor thesis focuses on the topic of identity of Native Americans in the novel Indian Killer by the Native author Sherman Alexie. The paper provides literary context of Native American writing and in more detail explains the terms "identity" and "ethnicity". The thesis subsequently analyzes the novel Indian Killer and examines how the author portrays the issue of identity and ethnicity of Native Americans in modern society.
Identita v díle Indian Killer Shermana Alexieho
Keywords: Native Americans; Alexie, Sherman; identity; ethnicity; američtí Indiáni; Alexie, Sherman; identita; etnicita